Molecular Dynamics Simulation Of Polyhydroxyalkanoate Synthase From Chromobacterium Sp. Usm2 - Annamalai, Nithyanan (2019)
Polyhydroxyalkanoate synthase from locally isolated organism, Chromobacterium sp. (PhaCCs) has been reported as a highly active enzyme in its natural form that is able to produce PHA that have better mechanical and thermal properties compared to the commonly produced P(3HB) homopolymer. In an attempt to understand the dimerization of PhaCC, a research been done to predict the monomer and dimer model the PhaCCs. Based on the result obtain via site-directed mutagenesis, it has been postulated that mutation of residue Arg409Ala and Arg490Ala of the PhaCCs disrupt the formation of PhaCCs dimer. However, it is completely unknown how this mutation affects the structure, stability, dynamics, and binding function of the PhaCCs protein. In this research study, molecular dynamics simulation approach has been utilized to address these issues. From the simulation analysis of the native and proposed mutant structures of both monomer and dimer of PhaCC, it has been found that mutation of R409A and R490A has disrupted the hydrogen bond interaction of His404 and Gly480 and the salt bridge interaction between Arg490 and Asp488 respectively which leads to the disorientation of the catalytic triad position of PhaCCs. In addition, the results also demonstrated that there is no direct involvement of Arg409 and Arg490 in dimerization of PhaCCs.